Neural Indices of Emotion Regulatory Implementation Correlate With Behavioral Regulatory Selection: Proof-of-Concept Investigation - Fine, Naomi B.; Schwartz, Naama; Hendler, Talma; Gonen, Tal; Sheppes, Gal (Frontiers in Behavioral Neuroscience, 2022)
“Do what you do best” conveys an intuition about the association between ability and preference. In the field of emotion regulation, ability and preference are manifested in two central stages: implementation and selection of regulatory strategies, that to date have been mainly studied separately. Accordingly, the present proof-of-concept study wished to provide preliminary evidence for an association between neural indices of implementation ability and behavioral selection preferences. In this pilot study, participants performed a classic neuroimaging regulatory implementation task that examined their ability (neurally reflected in the degree of amygdala modulation) to execute two central regulatory strategies: attentional distraction and cognitive reappraisal while viewing negative images. Then participants performed a separate, classic behavioral selection task that examined their choice preferences for using distraction and reappraisal while viewing negative images. Confirming our conceptual framework we found that exclusively for distraction, that has been associated with robust amygdala modulation, a decrease in amygdala activity during implementation (i.e., enhanced ability) was associated with enhanced preference to behaviorally select distraction (r (15) = -0.69, p=0.004). These preliminary findings link between two central emotion regulatory stages, suggesting a clue of the adaptive association between neural ability and behavioral preference for particular regulatory strategies.